Due storie d’acqua in Shakespeare: Ofelia e Narciso tra Pitagora e Ovidio - Lombardi, Chiara (Status Quaestionis, 2018)
The essay aims at analyzing two stories of water in Shakespeare: the tragic death of Ophelia in Hamlet, and the myth of Narcissus implicitly evoked in the Sonnets. Both may be read not only according to the Ovidian representation of the passions, as has already been significantly shown (for example by Bate 1991, and Enterline 2006 and 2012), but also in light of a relationship with the Pythagorical philosophy underlying the same conceptual frame of the Ovidian Metamorphosis. I would like to show that, behind the Pythagorical symbology of water, whose movement is conceived at the same time as a conclusive act, and as a flow always renewing itself in a world of fluid images, we may find a different perspective on Shakespearian aesthetics and the late Renaissance view of humankind and art.